Isolation and screening of wood-decaying fungi for lignocellulolytic enzyme production and bioremediation processes - Civzele, Anna; Mezule, Linda (Frontiers in Fungal Biology, 2024)
The growing demand for novel enzyme producers to meet industrial and environmental needs has driven interest in lignocellulose-degrading fungi. In this study, lignocellulolytic enzyme production capabilities of environmental fungal isolates collected from boreal coniferous and nemoral summer green deciduous forests were investigated, using Congo Red, ABTS, and Azure B as indicators of cellulolytic and ligninolytic enzyme productions. Through qualitative and quantitative assays, the study aimed to identify promising species for lignocellulose-degrading enzyme secretion and assess their potential for biotechnological applications. Primary screening tests showed intensive enzyme secretion by certain isolates, particularly white rot fungi identified as Trametes pubescens and Cerrena unicolor. These fungi exhibited high efficiency in degrading Congo Red and Azure B. The isolates achieved up to a 93.30% decrease in Congo Red induced color intensity and over 78% decolorization of Azure B within 168 hours. Within 336 hours, these fungi reached nearly 99% removal of Congo Red and up to 99.79% decolorization of Azure B. Enzyme activity analysis confirmed the lignin-degrading capabilities of T. pubescens, which exhibited laccase activity exceeding 208 U/mL. Furthermore, Fomitopsis pinicola showed the highest cellulose-degrading potential among the studied fungi, achieving cellulase activity over 107 U/L during Congo Red decolorization. Previously undescribed enzyme-producing species, such as Peniophora cinerea, Phacidium subcorticalis, and Cladosporium pseudocladosporioides, also demonstrated promising lignocellulolytic enzyme production potential, achieving up to 98.65% and 99.80% decolorization of Congo Red and Azure B, respectively. The study demonstrates novel candidates for efficient lignocellulolytic enzyme production with broad biotechnological applications such as biomass conversion, wastewater treatment, textile dye and other complex chemical removal, and environmental remediation.